Online Learning Problems for Elementary School Students - Widikasih, Putu Astri; Widiana, I Wayan; Margunayasa, I Gede (LPPM Undiksha, 2021)
The existence of the Covid-19 pandemic causes the implementation of learning can not be done face-to-face but only through online media with an online learning model that poses various obstacles felt by students. This study aims to examine what problems experienced by elementary school students in online learning based on these problems. The type of research used is descriptive research using quantitative data analysis techniques. The population in this study was 401,321 students. In this study, 2 sampling techniques were used: random cluster sampling and accidental sampling with the final sample count of 1,104 students. In this study, data collection was conducted by giving questionnaires to respondents, then analyzed using a percentage formula with quantitative analysis. The findings in this study show that there are 8 problems experienced by elementary school students in online learning during the pandemic, including the lack of comfort of students when attending online learning, low digital literacy skills of students, students have not been able to adapt well, students do not have adequate learning tools, lack of availability of supporting costs, students difficult to understand the subject matter, and low learning motivation. This research is expected to positively influence the improvement of the implementation of education and was expected to be a foundation in the development of science and technology education.